Effects of embedded acceptance and commitment training in veterinary medical and technology programs as students transition into the workforce: A study protocol - Mary Beth Spitznagel; John Martin; Nikki E. Bennett; Christopher Was; Christopher M. Fulkerson; Jim Weisman; Luca Giori; Erin Kelly-Snyder; Alanna S. G. Updegraff; Michael P. Twohig; Michael E. Levin (PLoS ONE, 2025)
Psychological distress is elevated in the field of veterinary medicine. Recent evidence demonstrates that stress and burnout in veterinary workers can be reduced through an Acceptance and Commitment Training intervention targeting “burden transfer,” or reactivity to challenging interactions with veterinary clients (“Unburdened”). Exposing students to Unburdened could optimize mental health outcomes as they transition into the veterinary workforce. Unburdened will be adapted for student use in a self-guided digital format and embedded into 5 veterinary medical or technology programs. Participants will be 200 advanced students recruited into a parallel-arms design: assessment-only Control versus Intervention (<2 hour Unburdened intervention embedded into final semester requirements) conditions. Online assessments at baseline, program completion (1 month), and follow-up (3, 6, 9, 12 months) will measure Kirkpatrick outcomes: Reaction (engagement, perception of the program), Learning (knowledge test performance), Behavior (skill use frequency), and Results (burden transfer, stress, burnout, anxiety, and depression). Latent growth curve modeling will compare conditions throughout the year following graduation. Institutional Review Board approval has been obtained. Informed consent is electronically granted by students electing to participate. A safety officer unconnected to the study will monitor study progress and safety. Pending positive outcomes, this ready-to-share program will be made available to training programs. If successful, its routine adoption into training curricula could decrease burden transfer, stress, burnout, anxiety, and depression in the field. Ultimately, the proposed work could provide a scalable and sustainable strategy to enhance mental health and well-being across the veterinary workforce. Study registration: The trial to evaluate Unburdened’s potential impact on mental health is considered observational, as the involved educational institutions chose to implement the program for its educational value. Details can be found in NIH RePORTER: https://reporter.nih.gov/search/FhAMx6slrEautC8YKesk0Q/project-details/10980628 . This study is registered with the Open Science Framework, where data will ultimately be made available: DOI 10.17605/OSF.IO/QEAKM.